The Influence of Subluxation on the Severity of Symptoms, Disability, and the Results of Operative Treatment in TMC Osteoarthritis with Total Joint Arthroplasty. (December 2015) - Larsen, Solveig K. A.; Østergaard, Ann Mai; Hansen, Torben B.
Background: The role of subluxation in staging of the severity of osteoarthritic changes remains unclear. The aim of this study was to evaluate the influence of subluxation of symptomatic osteoarthritic trapeziometacarpal (TMC) joint regarding severity of symptoms, disability, and results of operative treatment in TMC osteoarthritis with total joint arthroplasty. Methods: We included 172 hands in 137 patients (32 males and 105 females), mean age 59 years (44–74 years), with a combination of radiological signs of TMC osteoarthritis and clinical symptoms in the study. All patients were operated in general anaesthesia where a ball and socket joint implant was used. Disability of the Arm, Shoulder and Hand (DASH) score, visual analog scale, grip strength, and abduction deficiency were recorded and subluxation was measured on computed tomography. Results: The mean subluxation in males was 5.2 mm (SD 1.2) and in females 5.3 mm (SD 1.3) (p=0.95). We found a weak positive correlation between grip strength and subluxation both at the preoperative examination and at 3 and 12 months after the operation, but no other correlations with subluxation were found. Conclusions: This study indicates that radial subluxation may not be an important factor in symptoms and function in patients with symptomatic TMC osteoarthritis without severe scaphotrapezio (ST) joint degeneration. In addition, preoperative subluxation seems not to be important for the result after total joint arthroplasty.